2013
DOI: 10.1080/19376812.2012.746093
|View full text |Cite
|
Sign up to set email alerts
|

More people, more trees in South Eastern Tanzania: local and global drivers of land-use/cover changes

Abstract: Land degradation in South Eastern Tanzania, the country's major cashew producing area, has been attributed to deforestation. By comparing land-use/cover maps derived from aerial photographs of 1965 with maps derived from satellite images of 2002, we assessed how land-use changed in six villages, and relate these to local and global drivers. Land-use/cover changes are complex processes, which we analyzed by determining the relative net changes, losses, persistence and gains of each land-use/cover categories. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The situation in Kilwa and Lindi appear to be parallel to findings reported in a study from Makonde plateau, in south-eastern Tanzania (Kabanza et al, 2013) where the spread of commercial cashew production has led to substantial forest and land use changes. Increasing international demand for cashew nuts, combined with population growth and the villagisation program, have led to widespread transformation of land use since the 1960s.…”
Section: Discussionsupporting
confidence: 75%
“…The situation in Kilwa and Lindi appear to be parallel to findings reported in a study from Makonde plateau, in south-eastern Tanzania (Kabanza et al, 2013) where the spread of commercial cashew production has led to substantial forest and land use changes. Increasing international demand for cashew nuts, combined with population growth and the villagisation program, have led to widespread transformation of land use since the 1960s.…”
Section: Discussionsupporting
confidence: 75%
“…From the perspective of forest cover change, Reusing (); Mekuria (); Bedru (); Dereje () and Belay () are in agreement with the identified causes of Geist & Lambin (); Lambin et al () and Kabanza et al (), who showed that forest cover changes are driven by a complex of underlying causes rather than by single factors such as ‘shifting cultivation’ or ‘increasing population’ pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kikula () indicated that the villagisation programme in Tanzania has had long‐term negative environmental impacts such as forest cover decrease and land degradation. Kabanza et al () also showed that villagisation resulted in a decline in forest cover in the Makonde plateau in southeastern Tanzania, even though the villagisation policy was enacted with the intention to reduce the impact on the forests and to provide collective social services. However, villagisation works only when the people consent to the programme; otherwise, it has a strong impact on the environment by alternating the utilisation of resources in the new and in the previous place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the consistently high global demand for cashew and its products, it is possible that the demand for cashew could lead to significant socio-environmental costs in the tropics, as has been documented for superfoods Cho et al, 2021). Evidence shows that cashew cultivation has expanded over native forests, savannah woodlands, and rice fields across Brazil, Guinea-Bissau, Benin, Burkina Faso, Tanzania, Cambodia, Laos and Vietnam (Augusseau et al, 2006;Barry ed., 2007;Boubacar-Sid et al, 2007;Ntongani et al, 2010;Dinh et al, 2010;Temudo & Abrantes 2013;Kabanza et al 2013;Hurni et al 2017;Temudo & Santos 2017;de Alencar et al, 2018;. A recent study by showed that cashew replaced forests, rubber, mixed farming, shifting cultivation, shrubs and grasslands in mainland tropical Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%